2010
DOI: 10.1007/s12031-010-9426-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of PKA and Epac on the Production of Cytokines in the Endotoxin-Stimulated Primary Cultured Microglia

Abstract: To further understand the anti-inflammatory effect of adenosine cyclic 3',5'-monophosphate (cAMP), we examined the effect of protein kinase A (PKA) and cAMP-responsive guanine nucleotide exchange factor (Epac) on the transcription and production of cytokines and on the activity of mitogen-activated protein kinases (MAPK) p38 and glycogen synthase kinase-3β (GSK-3β) in endotoxin-treated rat primary cultured microglia. The PKA specific agonist N6-benzoyladenosine-3,5-cAMP (6-Bnz-cAMP) not only inhibited the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Although cAMP level controls various cellular functions, the roles of cAMP in microglia remain to be elucidated. For example, the effects of cAMP increase on IL‐1β (Jin et al, ; Liu et al, ; Quan et al, ; Woo et al, ) and IL‐6 (Hashioka et al, ; Si et al, ) were different among studies. In contrast, almost all reports agreed that intracellular Ca 2+ concentration played a key role in cytokine production (Espinosa‐Parrilla et al, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cAMP level controls various cellular functions, the roles of cAMP in microglia remain to be elucidated. For example, the effects of cAMP increase on IL‐1β (Jin et al, ; Liu et al, ; Quan et al, ; Woo et al, ) and IL‐6 (Hashioka et al, ; Si et al, ) were different among studies. In contrast, almost all reports agreed that intracellular Ca 2+ concentration played a key role in cytokine production (Espinosa‐Parrilla et al, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38 has been shown to induce IL-10 expression in a microglial cell line upon adenosine administration [85]. However, in another study, a down-regulation on the activation of p38 in LPS-stimulated rat primary cultured microglia has been correlated with an enhancement in IL-10 prodution [121]. This controversy may be due to the different models used in both works, and/or to the distinct stimuli provided to microglial cells that may activate different molecular pathways.…”
Section: Molecular Mechanisms Regulating Il-10 Production In the Cnsmentioning
confidence: 99%
“…Cytokine and chemokine production in bone marrow-derived dendritic cells involves both Epac1 and PKA (58). It has also been reported that high concentrations of PKA and cell-impermeable Epac agonists play differential roles in the production of cytokines in primary cultured microglia stimulated with a high concentration of endotoxin (59). In our study, the actions of selective concentrations of both H89 (5 M) and the cell-permeable Epac agonist (10 M) suggest that cAMP-activated Epac rather than PKA mediates the effect of EP2 receptors on the expression of COX-2, iNOS, and inflammatory cytokines in classically activated rat microglia.…”
Section: Volume 288 • Number 13 • March 29 2013mentioning
confidence: 99%